(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Pregnancy is a very special time for a woman and her family, although being pregnant is a stressful condition for every woman. The COVID-19 pandemic has made that condition more stressful. Clinical trials prove that COVID-19 vaccines are safe for pregnant women and also for lactating mothers. So WHO has approved vaccines for both above-mentioned groups. Hence, Bangladesh Government has taken the decision to vaccinate every pregnant woman against COVID-19 infection. Objectives: To assess the side effects of COVID-19 vaccination on pregnant women in a tertiary care hospital in Bangladesh Army. Methods: This cross sectional single-centered observational study was conducted in Combined Military Hospital (CMH) Dhaka from August 2021 to November 2021. Total 50 pregnant nullipara and multipara women with double dose vaccination were included. Relevant data were recorded in a preformed data collection sheet and analyzed by SPSS version 20. Results: Mean age of the participants was 19.2±10.8 years. The most commonly observed symptoms were pain in injection site, fatigue, swelling in injection site and myalgia. The most prevalent affected age group were 25-35 years. Among 48 participants, 20(41.6%) had co-morbidites. Two participants were found to have COVID-19 infection (4%) after vaccination. Conclusion: Side effects profile obtained from pregnant women in this study were non-life threatening. A recognized vaccine programme can be a relieving factor for pregnant women from increased stress and anxiety caused by COVID-19. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 34-37